Prognostic value of radiographically defined extranodal extension in human papillomavirus‐associated locally advanced oropharyngeal carcinoma. Issue 9 (2nd May 2019) - Tian, Sibo; Ferris, Matthew J.; Switchenko, Jeffrey M.; Magliocca, Kelly R.; Cassidy, Richard J.; Jhaveri, Jaymin; Aiken, Ashley H.; Baugnon, Kristen L.; Hudgins, Patricia A.; Kendi, Ayse T. K.; Patel, Mihir R.; Saba, Nabil F.; et al.
Abstract: Background: Pathologic extranodal extension (ENE) has traditionally guided the management of head and neck cancers. The prognostic value of radiographic ENE (rENE) in human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (HPV + OPX) is uncertain. Methods: Patients with HPV + OPX with adequate pretreatment radiographic nodal evaluation from a single institution were analyzed. rENE status was determined by neuroradiologists' at time of diagnosis. Distant metastasis‐free survival (DMFS), overall survival (OS), and locoregional recurrence‐free survival (LRFS) were estimated using Kaplan‐Meier methods. Cox proportional hazards models were fit to assess the impact of rENE on survival endpoints. Results: Hundred sixty‐eight patients with OPX + squamous cell carcinomas diagnosed between April 2008 and December 2014 were included for analysis with median follow‐up of 3.3 years. Eighty‐eight percent of patients received concurrent chemoradiotherapy. rENE was not prognostic; its presence in patients with HPV + OPX did not significantly impact OS, LRFS, or DMFS. Conclusions: In patients with HPV + OPX, rENE was not significantly associated with OS, LRFS, or DMFS.